Students’ game addiction caused by multi-constructs and multi-dimensions: Self-controls, cognitive biases and opportunistic behaviours - Sumiyana, Sumiyana; Pratiwi, Inggit D. E.; Hadi, Caraka; Utami, Evy Rahman; Saputra, Muhammad Adlin (Frontiers in Education, 2022)
Purpose This study investigates some extant research concentrating on student self-regulation to play online games addictively. Then, it proposes a new design to explain game addiction caused by students’ cognitive biases according to three contested approaches: self-control or self-regulation, cognitive distortion, and opportunistic behaviour. Moreover, it separates each contested approach in detail. Research methodology This research generalises research subjects with specific qualities and characteristics according to the researchers’ provisions. It selects the population with specific attributes: self-control, cognitive bias, opportunistic behaviour, habits and addiction to online games. Then, this study distributes bilingual questionnaires to the respondents throughout Indonesia. Finally, it tests these research hypotheses, splits them according to each model, and avoids perfect-collinearity among the constructs. Originality This research creates a new design incorporating three contested models of students’ addiction to games. The authors argue that online game addiction is due to students’ weak self-control, cognitive distortion, and opportunistic behaviours. The first perspective suggests that students play games addictively because of their low self-control in managing their tasks and enjoying leisure time. Secondly, this research deals with students playing the game due to their cognitive distortions: embodiment, stereotype, and heuristic biases. Finally, the third perspective explains students’ addiction to games because of their probable attitudes and behaviours: indeterminism, escapism, and adverse selection. Findings This research finds that each contested model could explain students’ tendencies to be addicted to playing online games. The authors conclude that multi-constructs and multi-dimensions explain students’ tendency to play games addictively in all three contested models. Moreover, this research infers that students’ habits and addictive behaviours are due to the number of games available on social media and the internet. This availability would likely damage academic habits, behaviours, culture and environment. Meanwhile, educational systems cannot stop the emergence and alterations of some new games. Finally, this study innovates the multi-paradigm for teachers’ counselling guidance. Implications This study’s findings imply a need for students’ behavioural therapy to be conducted by academic counsellors who are careful of the causal factors of multi-constructs and multi-dimensions. Then, it argues that the different causal factors impact the need for different cognitive therapies. Moreover, it explains that equal treatment for these students addicted to games would make them more stressed. Then, academic counsellors developing healing and wellness programmes should mitigate these students with a specific trait from the subdimensions of each construct.